PELANGGARAN HAK CIPTA DALAM BISNIS DAN INDUSTRI MUSIK DALAM KOMUNIKASI MASSA - Ahmad Budi Sulistioyuwono, S.E, M.M, Ahmad Budi Sulistioyuwono, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2023)
The social norms and laws that govern society are taught using music as a medium. Because the composer must take into account and abide by the rules, ethics, and specific technical signs that are associated with music as a communication medium. However, it is believed that Indonesia's copyright legislation still pays scant attention to global competition and the explosive expansion of the creative industries. One of the areas of intellectual property that is most at risk from increasingly sophisticated violations carried out in line with the sophistication of computer technology is copyright. Due to plagiarism controversies that have occurred, many cases have affected a number of musicians in Indonesia. Many musicians acknowledge that they intentionally create music that is as similar as they can be because they have commercial goals because the stolen music sells well in the market. Mass communication studies have helped to identify plagiarism in the music industry, and improvements in information and technology have made it simpler for audiences to spot it.